2019
DOI: 10.2147/idr.s211746
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emergence of two <em>Escherichia coli</em> strains co-harboring <em>mcr-1</em> and bla<sub>NDM</sub> in fresh vegetables from China</p>

Abstract: BackgroundThe concurrence of mcr and carbapenemase genes among Enterobacteriaceae has been a great clinical concern. In our study, we aimed to investigate the prevalence of mcr-positive carbapenem-resistant Enterobacteriaceae (CRE) in fresh vegetables and shed light on the possibility of transmission of mcr-positive CRE via fresh vegetables.MethodsIn this study, 712 fresh vegetable samples from 10 provinces in China were collected between May 2017 and Dec 2018 and were screened for mcr and carbapenemase genes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…In this study, pAH25-1 was closely aligned with IncI2 plasmid pBA76-MCR-1 from E. coli in humans in the Arabian Peninsula (22). pAH62-1 was closely aligned with IncI2 plasmid pZJ3920-3 from E. coli in humans in Hangzhou, China, and pAH65-1 was closely aligned with IncI2 plasmid pP111 from Salmonella enterica serovar Typhimurium in pigs in Taiwan (23). This phenomenon emphasized that IncI2 plasmid posed a risk for the exchange of genetic material between different niches.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, pAH25-1 was closely aligned with IncI2 plasmid pBA76-MCR-1 from E. coli in humans in the Arabian Peninsula (22). pAH62-1 was closely aligned with IncI2 plasmid pZJ3920-3 from E. coli in humans in Hangzhou, China, and pAH65-1 was closely aligned with IncI2 plasmid pP111 from Salmonella enterica serovar Typhimurium in pigs in Taiwan (23). This phenomenon emphasized that IncI2 plasmid posed a risk for the exchange of genetic material between different niches.…”
Section: Discussionmentioning
confidence: 56%
“… 23 Moreover, an antimicrobial resistance gene conferring resistance to fosfomycin, fosA3 , is located upstream of NDM-9 region. To date, the emergence of bla NDM-9 has been reported in E. coli , 24 , 25 Klebsiella pneumoniae , 10 Klebsiella variicola , 11 and Cronobacter sakazakii . 26 Our discovery of this plasmid supplemented previous studies and further highlighted the dissemination of bla NDM-9 gene-carrying plasmids in human gut colonized isolates.…”
Section: Resultsmentioning
confidence: 99%
“…We detected ve strains of Acinetobacter and one strains of K. pneumoniae co-producing mcr-1 and NDM-5 in the present study. It has been reported that both bla NDM and mcr genes are commonly present in E. coli isolated from different sources [26][27][28][29], but the co-existence of the bla NDM and mcr genes in K. pneumoniae has rarely been reported. In this study, the plasmid harboring the mcr gene in K. pneumoniae was similar to other IncHI2-type plasmids present in E. coli, and upstream of the mcr gene was the common ISApl1 transposon.…”
Section: Discussionmentioning
confidence: 99%